The Systematics of Stable Hydrogen (δ2H) and Oxygen (δ18O) Isotopes and Tritium (3H) in the Hydrothermal System of the Yellowstone Plateau Volcanic Field, USA - Shaul Hurwitz; R. Blaine McCleskey; Bryant C. Jurgens; Jacob B. Lowenstern; Laura Clor; Andrew G. Hunt (Geochemistry, Geophysics, Geosystems, 2025)
Abstract To improve our understanding of hydrothermal activity on the Yellowstone Plateau volcanic field, we collected and analyzed a large data set of δ2H, δ18O, and the 3H concentrations of circum‐neutral and alkaline waters. We find that (a) hot springs are fed by recharge throughout the volcanic plateau, likely focused through fractured, permeable tuff units. Previous work had stressed the need for light δ2H water recharge restricted to the northern part of the plateau or recharge during past cold periods. However, new data from the Y‐7 drill hole suggests that recharge is not restricted to a certain area or a cold period. (b) δ18O values of thermal waters in the geyser basins are shifted from the global meteoric water line by temperature‐dependent water‐rock reactions with higher subsurface temperatures resulting in a greater shift. (c) Large temporal variations in the isotopic composition of meteoric water recharge and small temporal variability in the isotopic composition of hot spring discharge implies that the volume of groundwater in, and around the Yellowstone caldera is substantially larger than the volume of annual water recharge. (d) Hot springs discharged through different rhyolitic units correlate with identifiable differences in δ2H and δ18O compositions, 3H concentrations, and water chemistry that imply equilibration at different temperatures and travel along different flow paths. (e) Based on measured 3H concentrations, we calculate that hot spring waters in the central part of the geyser basins mostly contain <2% post‐1950 meteoric water, whereas waters discharged at the basin margins contain larger fractions of post‐1950s meteoric water.